Scientific Investigations of a 16th Century Stall Belonging to the Evangelic Church in Bistriţa, Bistriţa-Năsăud County, Romania. (30th December 2012) - Marutoiu, C.; Grapini, S. P.; Baciu, A.; Miclaus, M.; Marutoiu, V. C.; Dreve, S.; Kacso, I.; Bratu, I.
Abstract : The Evangelic Church in Bistriţa city is one of the important gothic monuments in Romania. Inside the church there have been preserved a series of furniture pieces from different centuries, and the stall that has been analysed in this study is one of them. The study presents the investigations that were made on the occasion of restoring the stall. The nature and the status of the wooden supports and also the composition of the painting layer which covers the front side of the stall were investigated by several methods: Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), and differential scanning calorimetry (DSC) analyses. The back side of the stall was made of spruce fir wood and its status was also investigated. The nature of the component elements and the heritage value of the ensemble were also established.